2019
DOI: 10.1080/13668803.2019.1599323
|View full text |Cite
|
Sign up to set email alerts
|

The importance of friends: social life challenges for foreign physicians in Southern Sweden

Abstract: The article connects the fields of work/non-work research with the research on social integration of migrants. It is based on in-depth interviews with foreign physicians in the south of Sweden which explored their work/non-work experiences and their subjective perceptions of managing work, family, social and private domains of life. Based on individual reflections of social life as experienced in the workplace, in the locations of everyday life and transnationally, the analysis does not pursue the existence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 48 publications
(66 reference statements)
5
20
0
1
Order By: Relevance
“…On the other hand, being unique in this way could also be seen as an opportunity to learn about Swedish culture and develop language skills. Previous research has acknowledged that being part of the community is an important dimension of quality in rural life [8] and for highly skilled migrants in general [38]. Our results add to previous research which has suggested that being able to have a social life is important.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…On the other hand, being unique in this way could also be seen as an opportunity to learn about Swedish culture and develop language skills. Previous research has acknowledged that being part of the community is an important dimension of quality in rural life [8] and for highly skilled migrants in general [38]. Our results add to previous research which has suggested that being able to have a social life is important.…”
Section: Discussionsupporting
confidence: 78%
“…Being integrated into a social context might therefore be important, but it would be difficult to achieve without cooperation from the surrounding community (cf. [38]). It is recommended that aspects other than just professional concerns could be included in further developments.…”
Section: Discussionmentioning
confidence: 99%
“…Perry (2018) found that employer-provided housing can generate negative coworker dynamics, thus aggravating workers' social isolation. In her work with migrant fast-food counter attendants in Alberta, Polanco (2016) similarly found that employer-supported pathways to permanent residence encourage workers to compete with each other for limited nomination spots, thereby engendering compliance in the workplace. Other researcher, on the other hand, have found that the forging of friendships among workers can provide an important mechanism for coping with social exclusion (Mayell, 2016).…”
Section: Discounting Relationships Under Canada's Tfwpmentioning
confidence: 98%
“…There is, however, a growing literature on particular professional categories and highly skilled migrants (c.f. Frykman & Öhlander 2018;Irastorza & Bevelander 2017) such as academics (Behtoui 2017;Mählck 2013;Olsson, Behtoui, & Leivestad 2018;Wolanik Boström 2005) and physicians (Frykman & Mozetič 2019;Wolanik Boström & Öhlander 2011, 2012, 2015 that may offer important insights into the topic. This diverse research shows that the pathways to advanced positions in the Swedish society are, in many respects, challenging (Sandelind & Ådahl 2010).…”
Section: Successful Migrants In Swedenmentioning
confidence: 99%